TWO TYPES OF REALIZATIONS OF MAKING REFUSAL IN SUNDANESE CONTEXT : A CASE STUDY - Euis Rina Mulyani (STKIP Siliwangi, 2013)
This study was motivated by the previous research which suggests that InIndonesian context, indirectness, especially when making a refusal, is viewedas an indication of politeness. The purpose of the present study is to find outwhether or not there are Indonesian (especially Sundanese ethnic) people whouse indirectness with doing both saving and ‘loosing face’ their addresseeswhen making refusal. The subjects of this study were some Sundanesepeople’s refusals in some natural conversations. Observation on people’snatural conversations was done in collecting data. This study employed qualitative analysis of data. The result of this study showed that therealization of making refusal in Sundanese can be grouped into two:expressed in indirectness with employing saving face only, andexpressed in indirectness with employing both saving face and ‘losingface’. The two types of refusal strategies used by Sundanese people arestill in Indonesian culture of politeness. KEYWORDS: Indirectness, politeness, saving face, and losing face